Localisation Training in Spain and Beyond: Towards a Consensus on Content and Approach - Sánchez Ramos, María del Mar; Torres del Rey, Jesús; Morado Vázquez, Lucía (HERMES - Journal of Language and Communication in Business, 2022)
Since localisation emerged in the 1980s as an activity linked to the software industry, its evolution has gone hand in hand with technological advances. In the globalised market of the 21st century, an ever-increasing range of digital products must be localised. While academic institutions are aware of how the increasing demand for localisation is affecting the translation industry, there is no consensus regarding what and how courses and modules on localisation should be taught. This article reports the findings of a survey-based study that adopted a descriptive-interpretive methodology to collect both quantitative and qualitative data from a group of 16 localisation trainers teaching on undergraduate translation programmes at Spanish universities. To contextualise and help with the focus of the survey, a literature review on localiser education was carried out. The results of both the survey and the literature review reinforce the findings of an earlier unpublished study by the same authors that localisation training is keeping pace with technological evolution, despite its scarce presence in translation studies curricula. In addition, respondents noted that one of their main challenges is finding authentic teaching materials and recommended closer collaboration between academia and the localisation